Role of Bone Marrow Stromal Cells in Impaired Bone Repair from BRONJ Osseous Lesions. (May 2017) - He, L.H.; Xiao, E.; An, J.G.; He, Y.; Chen, S.; Zhao, L.; Zhang, T.; Zhang, Y.
Treatment of bisphosphonate-related osteonecrosis of the jaw (BRONJ) has posed significant challenges to maxillofacial surgeons because of the poor repair of BRONJ bone defects. Moreover, the pathological mechanisms remain unclear. Bone marrow stromal cells (BMSCs) play key roles during bone repair and bone regeneration. However, the activities of BMSCs derived from BRONJ lesions and the BRONJ lesion boundary, as well as the roles of BMSCs in BRONJ defect repair, are poorly defined. In this study, we found that BMSCs from the central area of the osteonecrotic BRONJ region (center-BRONJ BMSCs) and the peripheral area at the recommended debridement boundary (peri-BRONJ BMSCs) had decreased proliferative ability, self-renewal capacity, and multidifferentiation capacities compared with control BMSCs. Osteoclast-inducing ability was also impaired in BRONJ BMSCs. All of these results suggested that the decreased activities of BRONJ BMSCs, even the BMSCs derived from the BRONJ lesion boundary, might be an important factor leading to insufficient bone repair of BRONJ lesions. This study offers early stage evidence for the use of marrow stromal cells in the treatment of BRONJ.